Expressive Writing with "Jurnaling Technique": Client's Self Exploration Strategy - Ilham Khairi Siregar (JAMBURA Guidance and Counseling Journal, 2020)
This article contains a number of research results which are summarized into a meta-analysis paper. Some research results cover the application of journaling counseling techniques in a broad scope. Counseling services become a very important requirement to be implemented in the Education unit, especially higher education. Journaling counseling technique is one of the service efforts provided to clients, so clients can explore, express emotions and pressures, and analyze them into a coherence that can develop the client's personality. The author hopes that this article will be a reference source in alleviating client problems and the application of supporting literature display activities.